Detection and identification of Naegleria species along with Naegleria fowleri in the tap water samples - Muhammad Aurongzeb; Syeda Zehratul Fatima; Syed Ikhlaq Hussain; Yasmeen Rashid; Tariq Aziz; Majid Alhomrani; Walaa F. Alsanie; Abdulhakeem S. Alamri (BMC Medical Genomics)
Abstract Naegleria fowleri, the causative agent of Primary Amoebic Meningoencephalitis (PAM), is commonly found in warm freshwater environments and can enter the brain through nasal passages during activities like swimming or ablution. PAM has a high fatality rate, raising concerns about its global health impact. In Pakistan, particularly in Karachi, a significant number of cases have been reported, often with no history of recreational water exposure, but with regular ablution using tap water. This study analyzed the physicochemical parameters, abundance of total and fecal coliforms, and detected N. fowleri and other Naegleria species in tap water samples from Karachi using PCR with ITS- and Naegl-primers. Almost all samples exhibited high temperatures, low chlorine levels, and a high presence of coliforms. N. fowleri and other Naegleria species were detected in 11 out of 39 samples. Sequence analysis identified N. fowleri in tap water from the Golimar and Lyari areas of Karachi, while the other nine samples revealed different Naegleria species. This study suggests that the combination of high temperatures, insufficient chlorination, and the presence of coliforms may create favorable conditions for N. fowleri growth. However, these factors are not exclusive to the Golimar and Lyari areas, indicating that other environmental or infrastructural factors, not detailed in this study, may have contributed to the presence of N. fowleri in that specific location.